Mechanical properties of biocompatible clay/P(MEO2MA-co-OEGMA) nanocomposite hydrogels. (August 2017) - Xiang, Hengxue; Xia, Mengge; Cunningham, Alexander; Chen, Wei; Sun, Bin; Zhu, Meifang
Abstract: The effects of crosslinking density, polymer concentration and monomer ratio on the mechanical properties (tensile and compressive properties) of biocompatible clay/P(MEO2 MA- co -OEGMA) nanocomposite (NC) hydrogels were investigated. These novel NC hydrogels, composed of inorganic/organic networks, were prepared via in-situ free radical polymerization. The results showed that with increasing inorganic crosslinking agent, i.e. clay concentration, an increase in the tensile strength, elongation at break and compressive strength was observed. Similarly, with increasing polymer concentration, the tensile strength and compressive strength of the NC hydrogels increased while the elongation at break decreased. Increasing the molar concentration of OEGMA in the comonomer led to an increase in the tensile strength of the NC hydrogels but a reduction in the compressive strength. Moreover, clay/P(MEO2 MA- co -OEGMA) NC hydrogels presented good biocompatibility bolstering their application as tissue engineering scaffolds. Highlights: The clay/P(MEO2 MA- co -OEGMA) is a kind of physical nanocomposite (NC) hydrogels. The resultant NC hydrogels possess robust mechanical properties. The NC hydrogels have a potential application in tissue engineering.